2019
DOI: 10.3390/ijms20246273
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Role of HDL-Associated Sphingosine-1-Phosphate in Cardiometabolic Diseases

Abstract: Sphingolipids are key signaling molecules involved in the regulation of cell physiology. These species are found in tissues and in circulation. Although they only constitute a small fraction in lipid composition of circulating lipoproteins, their concentration in plasma and distribution among plasma lipoproteins appears distorted under adverse cardiometabolic conditions such as diabetes mellitus. Sphingosine-1-phosphate (S1P), one of their main representatives, is involved in regulating cardiomyocyte homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 259 publications
(397 reference statements)
1
14
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Endothelium and erythrocytes contribute, primarily, to the plasma pool of S1P, and the apoM-component of high-density lipoprotein (HDL) is the major carrier in plasma. 5,13 Not surprisingly, S1P and HDL-bound S1P are reduced in pathologies or conditions associated with endothelial injury, including diabetes, [14][15][16][17][18][19][20][21] metabolic syndrome, 22 myocardial infarction, 20,21 sepsis, 23,24 in-stent restenosis, 25 and in coronary and peripheral artery disease. 26 In patients with cardiovascular disease, higher S1P is associated with cardioprotective settings such as preinfarction angina 27 and coronary collateral circulation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Endothelium and erythrocytes contribute, primarily, to the plasma pool of S1P, and the apoM-component of high-density lipoprotein (HDL) is the major carrier in plasma. 5,13 Not surprisingly, S1P and HDL-bound S1P are reduced in pathologies or conditions associated with endothelial injury, including diabetes, [14][15][16][17][18][19][20][21] metabolic syndrome, 22 myocardial infarction, 20,21 sepsis, 23,24 in-stent restenosis, 25 and in coronary and peripheral artery disease. 26 In patients with cardiovascular disease, higher S1P is associated with cardioprotective settings such as preinfarction angina 27 and coronary collateral circulation.…”
Section: Introductionmentioning
confidence: 99%
“…HDL-associated S1P is less susceptible to degradation than free S1P or S1P bound to albumin, suggesting an important role of HDL in regulating the uptake, systemic function and cellular degradation of S1P. Although the mechanism of S1P efflux from cells to HDL is not clearly established, it involves specific transporters, such as adenosine triphosphate (ATP)-binding cassette family transporters [ 56 , 57 , 58 ], including ATP-binding cassette subfamily A member 1 (ABCA1) [ 59 , 60 , 61 ]. S1P plays a central protective role in the pathogenesis of many inflammatory disorders, including asthma, rheumatoid arthritis and atherosclerosis, through modulation of endothelial barrier function [ 62 , 63 , 64 , 65 ] and macrophage function [ 66 ].…”
Section: Immunomodulatory Functions Of Hdlmentioning
confidence: 99%
“…S1P also has an atheroprotective effect during the progression of atherosclerosis. The antiatherogenic effect of S1P may partially depend on specific action of sphingosine 1 phosphate receptor 1-4 (S1PR1-4) in various types of cells [ 57 ]. It was shown that activation of S1PR1, which is a G-protein receptor, and presence of HDL, which is the main carrier of S1P, can protect macrophages from apoptosis.…”
Section: The Role Of Er Stress In Apoptosismentioning
confidence: 99%